Copper-catalyzed borylation of cycloalkylsilyl peroxides via radical C–C bond cleavage. Issue 15 (1st July 2019) - Yang, Jun-Cheng; Chen, Lei; Yang, Fan; Li, Pengfei; Guo, Li-Na
Abstract : A mild copper-catalyzed radical C–C bond cleavage/borylation of cycloalkylsilyl peroxides is described. A range of four to eight, and even twelve-membered substrates were compatible, offering rapid access to keto-functionalized alkyl boronic esters. Abstract : A copper-catalyzed radical C–C bond cleavage/borylation of cycloalkylsilyl peroxides has been developed under mild conditions. A broad range of four-, five-, six-, seven-, eight- and twelve-membered cycloalkylsilyl peroxides were compatible with this transformation, which offers rapid access to primary and secondary keto-functionalized alkyl boronic esters.